Trabecular meshwork ultrastructural changes in primary and secondary glaucoma - Aparna Rao; Tirupathi Rao; Nagapriya Banka; Sirisha Senthil; Saumya Jaketi (Scientific Reports)
Abstract To examine ultrastructural changes in the trabecular meshwork (TM) in patients with primary and secondary glaucoma using scanning electron microscopy (SEM). This was a qualitative descriptive hospital-based study on the ultrastructure of the TM. Pure TM samples were collected after microincisional trabeculectomy from 26 patients with primary or secondary glaucoma and 10 control samples from eye bank donor corneas. SEM was used to analyze structural changes in the TM beams, corneoscleral meshwork (CSM), and juxtacanalicular (JCT) regions. Morphological features were compared between groups and correlated with histopathological findings. SEM revealed flattened and broadened TM beams in the JCT, resembling controls, often with a dumbbell configuration. Histopathological examination (HPE) and SEM showed rounded TM beams with considerable thinning, especially in primary angle-closure glaucoma (PACG), compared to primary open-angle (POAG) and pseudoexfoliation glaucoma (XFG). Maximum thinning in all primary glaucoma occurred in the CSM region, with minimal changes in the JCT region despite a reduction in cellularity in both regions. In steroid glaucoma, amorphous, glistening material was found on the TM beams in the JCT and CSM. XFG eyes displayed vesicular bodies adjacent to fibrillar material scattered diffusely over the TM beams, particularly in the CSM, differing from the platelet clumps seen in regular blood clots. TM beam thinning in primary glaucoma primarily affects the CSM region, sparing the JCT region. Amorphous deposits or vesicular bodies, seen only in steroid-induced glaucoma and XFG, suggest different mechanisms of TM damage in these glaucoma types.